Morfološka variabilnost črnike (Quercus ilex L.) v Sloveniji - Martin Jež; Robert Brus; Kristjan Jarni (Acta Silvae et Ligni)
This article introduces the holm oak (Quercus ilex L.), one of the most important tree species of the Mediterranean flora in Slovenia. In Slovenia, it grows in scattered locations at the northern limit of its natural range. The main aim of the study was to investigate the morphological variability of its leaves. Seven natural populations of holm oak in Slovenia were included in the study. The morphometric analysis showed high leaf variability and significant differences between populations, which were confirmed for almost all morphological traits analysed. Based on the observed morphological differences, the Slovenian populations can be divided into three geographical-morphological groups: i) the populations in the Goriška region (Sabotin, Sv. Gora and Lijak), ii) those in the Nanos – Osp region and iii) those in the Dragonja river valley. Morphological variability, as an expression of genetic variability, is the result of adaptation to specific local environmental conditions. The holm oak is currently not a threatened species in Slovenia, but it would be advisable to consider the three identified geographical-morphological groups as much as possible in any active conservation measures.